Influência das propriedades do pavimento aeroportuário na deformação elástica: Análise de modelagem com elementos finitos e infinitos para gerência de pavimentos - Silva, Gustavo Henrique Pinheiro da (2024)
The choice of materials when designing airport runways is fundamental to guaranteeing the operational safety of landings and take-offs, as well as defining the costs of construction or maintenance projects. To this end, it is necessary to understand how the characteristics of runway materials affect runway deformations in order to define design optimization strategies. The main objective of this Dissertation is to analyze whether there are elastic properties that should be prioritized in the design of airport runways. The research was carried out using a 3D finite element model in the ABAQUS 2020 software, with single axle, double tandem axle and triple tandem axle aircraft. In order to optimize the simulation runtime, the following were calibrated: the length of the simulated runway (25 simulations), the subgrade thickness adopted (25 simulations) and the size of the finite and infinite element meshes (1,728 simulations). In addition, 2,733 deformation simulations were carried out for the statistical analysis of runway characteristics. After the calibration simulations, 3.15m was taken as the thickness of the subgrade in an infinite element layer, and for the length of the simulated runway. Three partitioning element sizes were adopted for the model mesh: 0.05 m, 0.1 m and 0.5 m according to the proximity of the load application points. For the statistical analysis, the Bootstrap test was applied, which identifies the existence of statistically significant differences between the analysis parameters. The results show that the elastic variables have a different impact on the variation in deformation. In addition, the type of axle has a direct impact on the distribution of stresses and strains and should therefore be taken into account when prioritizing properties at the design stage. Finally, the most important variables for airport runway implementation and maintenance projects are the thickness of the surface, the modulus of elasticity of the base layer and the modulus of elasticity of the subgrade layer, in order of importance.